Mozart: Chamber Music with Clarinet - Vanoosthuyse, Eddy; Corstjens, Danny; Callaert, Geert; Zemlinsky Quartet (Antarctica, 2022)
Clarinet player Eddy Vanoosthuyse is joined by the renowned Czech Zemlinsky Quartet exhibiting a refreshing point of view on Mozart's repertoire for clarinet and string ensemble.All things Mozart have been said and done, you'd think. Well, nothing could be further from the truth. On a daily basis new findings are added to the research portfolio, not only with regards to the famous Salzburgian's life – hasn't that been dissected to death? – but also about each and every one of his compositions, continuously getting reframed, analysed and compared. The exegesis of the Mozartverse is a full-time job to many. The works on this recording alone raise a bunch of questions of which several remain unanswered.
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; Chamber music; Clarinet; Trio; String quartet